Effects of intermittent usage of water-based neomycin sulfate on the growth performance of weanling pigs - R O Gottlob; C R Neill; C N Groesbeck; K R Brown; N Z Frantz; Michael D Tokach; Robert D Goodband; Joel M DeRouchey; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2005)
A total of 360 weanling pigs (initially 11.4 lb and 18 ± 3 d of age, PIC) were used to determine the effects of intermittent use of water-based medication on nursery pig growth performance. Pigs were given one of eight experimental treatments: negative control (no antibiotics in the feed or water); positive control with Neo-TerramycinÂ® in the feed (140 g/ton Neomycin sulfate, 140 g/ton Oxytetracycline HCl); continuous use of either 38.0 or 75.5 mg Neomycin sulfate per L of water; use of either 38.0 or 75.5 mg of Neomycin sulfate per L of water, during weeks 1 and 3 after weaning; and use of either 38.0 or 75.5 mg Neomycin sulfate per L of water during weeks 2 and 4 after weaning. Overall (d 0 to 28 after weaning), pigs provided Neomycin sulfate in the water continuously and pigs fed the positive control diet had greater ADG (P<0.05) and ADFI (P<0.04) than did pigs provided non-medicated water and feed. Pigs fed the positive control diet tended (P<0.15) to have greater ADG than did pigs provided an intermittent supply of water-based Neomycin sulfate, but there was no difference in growth performance and feed efficiency between pigs fed the positive control diet and those provided a continuous supply of water-based Neomycin sulfate. Pigs provided a continuous supply of either dosage of Neomycin sulfate in the water had greater (P<0.05) ADG and ADFI than did pigs provided water-based Neomycin sulfate on an intermittent basis. These data demonstrate that providing neomycin in the feed or water results in a growth response, but there is no carryover effect. Thus, pig performance returns to the control level immediately after the supply of Neomycin is removed.; Swine Day, 2005, Kansas State University, Manhattan, KS, 2005
Keywords: Swine day; 2005; Summary Publication of Report of Progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 964; Kansas Agricultural Experiment Station contribution; no. 06-63-S; Nursery pig; Antibiotics; Water; Growth; Swine